2023
DOI: 10.17650/2070-9781-2023-24-2-126-129
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID changes of semen parameters: a new era for physical activity that needs investigation

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…ED may also be induced by unhealthy lifestyle factors, including smoking, alcohol consumption, insomnia, snoring, and lack of exercise. [2,3] Numerous clinical studies have confirmed that adopting healthy lifestyle changes could serve as an effective strategy to mitigate the risk of ED [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…ED may also be induced by unhealthy lifestyle factors, including smoking, alcohol consumption, insomnia, snoring, and lack of exercise. [2,3] Numerous clinical studies have confirmed that adopting healthy lifestyle changes could serve as an effective strategy to mitigate the risk of ED [4][5][6].…”
Section: Introductionmentioning
confidence: 99%